The Influence of Viral Marketing on Social Media and Online Customer Reviews on Purchase Decisions of Somethinc Cushion on the Shopee Marketplace in Banjarmasin - Nikita Constantia Josepine Huwei; Setio Utomo; M. Hasanur Arifin; Novia Nour Halisa (Magister Administrasi Bisnis ULM, 2025)
This research was conducted with the aim of testing and determining the partial and simultaneous influence of the Viral Marketing and Online Customer Review variables on the decision to purchase certain cushions at the Shopee Marketplace in Banjarmasin. This research uses a quantitative methodolgy. The research location is Banjarmasin City. The sample was 135 respondents who had purchased and used the Somethingnc cushion, with data collection using a questionnaire and data analysis using multiple linear regression analysis assisted by the IBM SPSS Statistics Version 25 program. The results of this research prove that Viral Marketing has a positive and significant influence on the Purchase Decision for Somethinc Cushions at the Shopee Marketplace in Banjarmasin. Online Customer Reviews have a positive and significant influence on the decision to purchase Somethinc Cushion at the Shopee Marketplace in Banjarmasin. As well as Viral Marketing and Online Customer Reviews have a positive and significant influence on the Purchase Decision of Somethinc Cushions at the Shopee Marketplace in Banjarmasin